2022
DOI: 10.1021/acs.chemmater.1c03821
|View full text |Cite
|
Sign up to set email alerts
|

LaRuSi Electride Disrupts the Scaling Relations for Ammonia Synthesis

Abstract: Electrides have shown their significant advantages in NH 3 synthesis as catalysts or supports under mild conditions. A better understanding of the unconventional reaction kinetics of electrides can greatly promote the development of this kind of novel catalyst. However, most electride-based catalysts are supported ones whose complexity hampers the mechanism study. In this article, the essence behind the catalytic performance of a LaRuSi electride was uncovered using a combination of experiments and first-princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Therefore, the steps of NH formation and NH 3 desorption over Ru/La–TM–Si should not take place on the Ru site. The idea of breaking scaling relations via multi-active sites (chemical looping) inspires us to consider a second site for NH x formation and NH 3 desorption. We took Ru/LaCoSi as an example and examined the activity of the TM site by computation. It turned out that the TM site in La–TM–Si is also inferior for NH x formation and NH 3 desorption (Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the steps of NH formation and NH 3 desorption over Ru/La–TM–Si should not take place on the Ru site. The idea of breaking scaling relations via multi-active sites (chemical looping) inspires us to consider a second site for NH x formation and NH 3 desorption. We took Ru/LaCoSi as an example and examined the activity of the TM site by computation. It turned out that the TM site in La–TM–Si is also inferior for NH x formation and NH 3 desorption (Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the presence of RE is indispensable for the outstanding supporting manner of ternary intermetallic electrides. Very recently, we found that the REs in the electrides are more than an electron donor [16,85]. La in LaTMSi (TM = Co, Fe, Ru, or Mn) is a better active site for the NH x formation and NH 3 desorption than the Ru site, which can help break the scaling relations on the Ru/LaTMSi catalysts.…”
Section: Re-based Electridesmentioning
confidence: 99%
“…Besides, they can alleviate or even avoid the H 2 poisoning effect, which is benefited from their strong H affinity that shunts H from Ru sites. Furthermore, the construction of the multi-sites (e.g., the Ru site or nitrogen-vacancy site for the N 2 activation [14,16], the Ni site for the H 2 activation [14], the RE site for the NH x formation [85]) would settle the competition of different elementary steps on one specific site. Recent studies have also revealed that the ammonia synthesis via an associative mechanism is preferable to the dissociative mechanism for a high-performance catalyst.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…There is, in addition, one further point to make that nitrate (NO 3 – ) pollution in natural resources is aggravated by anthropogenic nitrogen inputs, such as overapplication of agricultural fertilizers and discharge of industrial wastewater and municipal sewage. Therefore, efforts have been made to convert nitrate pollutants into other nitrogen species through biological nitrogen removal, chemical reduction, or electrocatalysis. An emerging research topic in the treatment of nitrate pollutants is to transform them into value-added chemicals [e.g., ammonia (NH 3 )]. It is universally acknowledged that ammonia is a momentous energy storage species and a clean CO x -free energetic vehicle. , At present, the proverbial Haber–Bosch process is principally applied to produce ammonia for industrial applications, and with that comes massive amounts of energy consumption. Electrochemical nitrate-to-ammonia conversion has been recognized as an emerging and promising technology. The electrochemical nitrate reduction to ammonia (NRA) involves eight-electron and nine-proton transfer, which not only significantly reduces the total kinetic rate but also generates other unnecessary byproducts in the reaction process. Concurrently, the hydrogen evolution reaction (HER) inevitably occurs. Based on the above considerations, there is a pressing demand for exploiting highly efficient catalysts for selective catalytic nitrate electroreduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%